Political turbulence and business as usual: tourism's future. Issue 1 (3rd April 2017) - Webster, Craig
Abstract : Purpose: The purpose of this paper is to discuss the political turbulence of the times and discuss how political movements and political events that appear to be shocking to many are linked with major transformations in the global economy in recent decades. The author shows how the political and economic situation will likely have little impact on tourism inflows in major developed countries in coming years. Design/methodology/approach: The paper explores global changes since the end of the Cold War and how this has impacted upon potential tourists in tourist source markets and host destinations. It is a global analysis, exploring changes since the Cold War. Findings: Western countries will continue to experience all sorts of political and social turbulence for the foreseeable future, as their populations become increasingly bifurcated in terms of their wealth and the fiat currency system and fractional reserve system of banking reaches the limits of what it is capable of. However, this does not necessarily mean that tourists will be deterred from travelling to developed countries, as long as the developed countries shield visitors from social upheaval and politically unpleasant events such as strikes, riots, and demonstrations. Practical implications: The practical implications are that managers in the tourism industry should become increasingly aware of the widening gap between the rich and poor in developed countries and prepare for the political and social shocks of dealing with this phenomenon. The phenomenon will have political expression in political movements that will pay lip service to populist demands but will also have expression in disappointed populations that will take part in social unrest of all sorts. Managers should prepare for various expressions of unrest in developed countries that had not been so widespread, including strikes, demonstrations, and riots. Originality/value: This paper discusses the ascendency of Donald Trump to the US Presidency and the increasing visibility of other political nonconformist movements in western countries as a possible threat to tourism in developed countries. It links the changing political and social reality of citizens since the end of the Cold War to the future role that developed countries will play in the tourism industry, largely as hosts to the world's affluent class created by globalization.